ANALISIS BIAYA PROMOSI TERHADAP TINGKAT PENDAPATAN JASA PADA HOTEL SUDI MAMPIR DI CIBITUNG - Ricky Pratama Simanjuntak (PARAMETER, 2020)
The main problem in this study is whether the promotional costs affect the income of the Sudi Mampir Hotel in Cibitung.The purpose of this study is to analyze the relationship and the influence of the promotion costs to the increase in income in the Sudi Mampir Hotel in Cibitung.The population in this study is the entire financial statement data of the Hotel Sudi Mampir for 5 years , namely 2014-2018 and the sample in this study was a number of population data of the promotional costs and income reports of Sudi Mampir Hotel for 5 years, namely 2014-2018.This study used a qualitative descriptive method consisting of two variables , namely costs promotion as the independent variable and income as the dependent variable.The data analysis technique used is simple linear regression , correlation coefficient analysis, determination coefficient analysis and t test. Based on the results of the regression analysis the equation Y = 152,9672 + 44,4075922X is obtained from this regression equation is positive this shows that the variable Y (income) will increase constantly if the variable X (promotion costs) is 0 means that each increase in the promotion cost variable by 1 unit will be followed by an increase in income by 3.444619%.From the results of the correlation analysis of 0 965166 , which means the relationship is very strong.The results of the coefficient of determination analysis show that the cost of promotion has an influence on income of 93.15447% and 6.84553% influenced by other variables not included in this study.Partially t count 6.389382 > t table 3,182.From the results of this study that the cost of promotion can increase revenue significantly and is very strong at Sudi Mampir Hotel.